CALIBRATION AND REFRAMING AS RAPPORT BUILDING TOOLS IN BUSINESS COMMUNICATION - GABRIELA DUMBRAVĂ (Annals of the University of Petrosani: Economics)
The paper approaches business communication as an instance of social intercourse built around multiple levels of negotiation that go deeper than the obvious economic aspect. In this context, concepts such as calibration and reframing are analysed as tools meant to adapt verbal and non-verbal interactions to a variety of interlocutors in order to establish a favourable context for communication, generically called ‘rapport’. Finally, the paper relies on the findings of research displayed in recent literature in order to approach the achievement, importance and benefits of building rapport on all business levels.